Cage egg producers' perspectives on the adoption of cage-free systems in China, Japan, Indonesia, Malaysia, Philippines, and Thailand - de Luna, Maria Catalina Tan; Yang, Qing; Agus, Ali; Ito, Shuichi; Idrus, Zulkifli; Iman, Rahayu H. S.; Jattuchai, Jutamart; Lane, Elissa; Nuggehalli, Jayasimha; Hartcher, Kate; Sinclair, Michelle (Frontiers in Veterinary Science, 2022)
Asia is responsible for approximately 60% of global egg production. As in most of the world, nearly all of the egg-laying hens are housed in cages. While there is growing demand for cage-free eggs in many regions of the world, challenges have been reported when transitioning to these systems, which may affect the willingness of producers to transition. The goals of this research were to investigate the views of cage egg producers on the feasibility of cage-free systems, the perceived main challenges in adopting cage-free systems, and proposed solutions. Questionnaires with a mix of free-form, Likert scale and demographic questions were distributed, and 165 cage egg producers completed the questionnaires. Data were analysed using thematic qualitative analysis and descriptive quantitative statistics. Responses indicated that cages are primarily used for their efficiency and ease of management. The most common reasons to consider adopting cage-free systems included improved animal welfare, market access, cost saving and product quality. Sixty-five percent of producers responded ‘yes’ or ‘maybe’ when asked if cage-free systems are feasible. Perceived challenges in adopting cage-free systems included reduced profitability, higher costs, and biosecurity and disease. Potential solutions included the development of the cage-free industry and market development. Most producers (72%) said more support is needed to establish cage-free farms, mostly in technical advice, training and resources, and is particularly needed from the government. The findings of this study provide an enhanced understanding of the egg industry in these countries and potential areas for producer support in transitioning to cage-free systems.